Effect of Organomontmorillonite-Cloisite® 20A Incorporation on the Structural and Drug Release Properties of Ureasil–PEO Hybrid - Jesus, Celso R. N. [UNESP]; Molina, Eduardo F.; de Oliveira, Ricardo; Pulcinelli, Sandra H. [UNESP]; Santilli, Celso V. [UNESP] (My University, 2023)
This paper presents the influence of the presence of a modified organoclay, Cloisite® 20A (MMTA) on the structural and drug release properties of ureasil organic–inorganic hybrid. Sol–gel process was used to prepare the hybrid nanocomposites containing sodium diclofenac (DCF) at 5% wt. The effect of the amount of MMTA incorporated into the ureasil hybrid matrix was evaluated and characterized in depth by different techniques such as X-ray diffraction (XRD), small angle X-ray scattering (SAXS), differential scanning calorimetry (DSC), and swelling properties. The influence of MMTA on ureasil nanocomposites release profile was evaluated by in situ UV–vis. The diffraction patterns of the UPEO–MMTA nanocomposites showed a synergistic contribution effect that led to an intensity increase and narrowed the diffraction peaks, evidencing a crystallite PEO growth as a function of the modified nanoclay content. The interactions between polyether chains and the hydrogenated tallow of MMTA led to an easy intercalation process, as observed in UPEO–MMTA nanocomposites containing low (1% wt) or high (20% wt) nanoclay content. The waterway (channels) created in UPEO–MMTA nanocomposites contributed to a free volume increase in the swollen network compared to UPEO without MMTA. The hypothesis of the channels created after intercalation of the PEO phase in the interlayer of MMTA containing organoammonium ions corroborates with the XRD results, swelling studies by SAXS, and release assays. Furthermore, when these clay particles were dispersed in the polymeric matrix by an intercalation process, water uptake improvement was observed, with an increased amount of DCF release. The design of ureasil-MMTA nanocomposites containing modified nanoclay endows them with tunable properties; for example, swelling degree followed by amount of controlled drug release, opening the way for more versatile biomedical applications.
Keywords: drug release; nanocomposite; organoclay; ureasil-polyether